Hyphaema in phacolytic glaucoma, a case report. - Suhardjo Suhardjo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Background: Phacolytic glaucoma is a secondary glaucoma which occurs in open angle hypermature cataract and caused by trabecular obstruction. This abstruction occurs due to the leaked of lens protein through an intact capsule. Hyphaema in phacolytic glaucoma is an unusual case.Objective : To evaluate the result of conservative therapy and extra capsular cataract extraction on phacolytic glaucoma associated with hyphaema.Methods :A case of hyphaema in phacolytic glaucoma has been reported in a 62 year old man. Symptoms of decreased visual acuity, pain, headache were found in this case. Ophthalmology examination found right visual acuity 1/", light projection and color perception good, conjunctival hyperaemia, ciliary injection, corneal edema, hyphaema, opacity of anterior chamber, iris atrophy, posterior synechiae, and increased intraocular pressure. This case was treated conservatively and cataract surgery was also done accordingly.Result: The result of treatment was loss of vitreous resulted from rupture of posterior capsule, decreased of intraocular pressure.Conclusion : Conservative therapy and extra capsular cataract extraction can improve visual acuity in phacolytic glaucoma associated with hyphaema.Key words: hyphaema - phacolytic glaucoma - conservative and cataract surgery - vitreous loss.